2007
DOI: 10.1029/172gm18
|View full text |Cite
|
Sign up to set email alerts
|

Diverse deformation patterns of Aleutian Volcanoes from satellite Interferometric Synthetic Aperture Radar (InSAR)

Abstract: Interferometric synthetic aperture radar (InSAR) is capable of measuring groundsurface deformation with centimeter-to-subcentimeter precision at a spatial resolution of tens of meters over a large region. With its global coverage and all-weather imaging capability, InSAR has become an increasingly important measurement technique for constraining magma dynamics of volcanoes over remote regions such as the Aleutian Islands. The spatial distribution of surface deformation data derived from InSAR images enables th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
(64 reference statements)
0
21
0
1
Order By: Relevance
“…A better analog for the Three Sisters activity might be found at one or more volcanoes in the Aleutian arc, where InSAR studies have revealed numerous cases of ground deformation at relatively small volcanic centers (Lu et al 2007). Westdahl shield volcano, for example, re-inflated following its 1991-1992 effusive eruption at an exponentially declining rate with a 1/e decay constant of~6 yearssimilar to the 5.3 ± 1.1 years time constant for Three Sisters that we report here.…”
Section: Discussionmentioning
confidence: 98%
“…A better analog for the Three Sisters activity might be found at one or more volcanoes in the Aleutian arc, where InSAR studies have revealed numerous cases of ground deformation at relatively small volcanic centers (Lu et al 2007). Westdahl shield volcano, for example, re-inflated following its 1991-1992 effusive eruption at an exponentially declining rate with a 1/e decay constant of~6 yearssimilar to the 5.3 ± 1.1 years time constant for Three Sisters that we report here.…”
Section: Discussionmentioning
confidence: 98%
“…InSAR maps of inter-eruption deformation, the onset of which often precedes swarms of earthquakes and other eruption precursors, provide insights into the structure, magma plumbing system and the state of restless volcanoes (e.g. Lu 2007, 2007b. InSAR also can be used to image ground surface displacements before, during and after large seismic events -information that is essential for hazard assessment and postdisaster response efforts.…”
Section: Hazards Applications Of Insar Deformation Mapsmentioning
confidence: 98%
“…InSAR maps of co-eruption deformation provide information about eruption dynamics, including the eruption rate as a function of time (e.g. Dzurisin 2003, Lu et al 2007b. InSAR maps of inter-eruption deformation, the onset of which often precedes swarms of earthquakes and other eruption precursors, provide insights into the structure, magma plumbing system and the state of restless volcanoes (e.g.…”
Section: Hazards Applications Of Insar Deformation Mapsmentioning
confidence: 99%
“…Fisher Caldera, which contains several active fumaroles and two large lakes, is one of the largest calderas in the Aleutian Islands [ Lu et al ., ] and is located east of Westdahl. The southern part of Fisher is covered by a thick layer of tephra, which offers the potential for achieving excellent coherence in InSAR studies.…”
Section: Unimak Island and Its Previous Geodetic Studiesmentioning
confidence: 99%